Toward Perovskite Solar Cell Commercialization: A Perspective and Research Roadmap Based on Interfacial Engineering - Rajagopal, Adharsh; Yao, Kai; Jen, Alex K.‐Y. (Advanced materials (Weinheim), 2018)
High‐efficiency and low‐cost perovskite solar cells (PVKSCs) are an ideal candidate for addressing the scalability challenge of solar‐based renewable energy. The dynamically evolving research field of PVKSCs has made immense progress in solving inherent challenges and capitalizing on their unique structure–property–processing–performance traits. This review offers a unique outlook on the paths toward commercialization of PVKSCs from the interfacial engineering perspective, relevant to both specialists and nonspecialists in the field through a brief introduction of the background of the field, current state‐of‐the‐art evolution, and future research prospects. The multifaceted role of interfaces in facilitating PVKSC development is explained. Beneficial impacts of diverse charge‐transporting materials and interfacial modifications are summarized. In addition, the role of interfaces in improving efficiency and stability for all emerging areas of PVKSC design are also evaluated. The authors' integral contributions in this area are highlighted on all fronts. Finally, future research opportunities for interfacial material development and applications along with scalability–durability–sustainability considerations pivotal for facilitating laboratory to industry translation are presented. The multifaceted roles of interfacial engineering in the evolution of highly efficient and stable perovskite solar cells are explained. Unique structure–property–processing–performance traits are summarized. Functions of diverse charge transport materials and interfacial modifications are comprehensively discussed. Scalability–durability–sustainability considerations for commercialization are highlighted. Prospective research directions are presented for all developmental fronts.